HIV cure research in South Africa: a preliminary exploration of stakeholder perspectives. Issue 4 (2nd April 2016) - Moodley, Keymanthri; Staunton, Ciara; de Roubaix, Malcolm; Cotton, Mark
ABSTRACT: Innovative strategies for HIV cure are in development and research studies are being designed and planned globally. South Africa is no exception. However, little is known about stakeholders' knowledge, understanding and expectations of future cure research. This study aimed to obtain in-depth qualitative insights into stakeholder perspectives at this formative stage of HIV cure research. Fifteen stakeholders were interviewed in an HIV research clinic in the Western Cape, South Africa with their consent. Interviews were transcribed verbatim and analysed using thematic content analysis. Broad themes that emerged included the meaning of cure, awareness of HIV cure research, risks and benefits of such research. General awareness and understanding of HIV cure research was lower than expected. Some participants expressed a fatalistic attitude to HIV and described it as an "end-time illness" with no prospect of cure. In general, HIV cure research was regarded as risky – biologically psychologically and socially. If study designs were to include treatment interruption, participants would comply only if success was guaranteed. Given these perceptions of HIV cure research, significant challenges to consent processes and participant recruitment can be anticipated. Authentic community engagement and intensive educational interventions will be necessary prior to future cure research in South Africa.